Use of the PROMIS Mobility score in assessing function in adolescents and adults previously affected by childhood hip disease. (21st December 2021) - Luo, Weisang; Ali, Mohammed S.; Limb, Richard; Cornforth, Christine; Perry, Daniel C.
Abstract : Aims: The Patient-Reported Outcomes Measurement Information System (PROMIS) has demonstrated faster administration, lower burden of data capture and reduced floor and ceiling effects compared to traditional Patient Reported Outcomes Measurements (PROMs). We investigated the suitability of PROMIS Mobility score in assessing physical function in the sequelae of childhood hip disease. Methods: In all, 266 adolscents (aged ≥ 12 years) and adults were identified with a prior diagnosis of childhood hip disease (either Perthes' disease (n = 232 (87.2%)) or Slipped Capital Femoral Epiphysis (n = 34 (12.8%)) with a mean age of 27.73 years (SD 12.24). Participants completed the PROMIS Mobility Computer Adaptive Test, the Non-Arthritic Hip Score (NAHS), EuroQol five-dimension five-level questionnaire, and the Numeric Pain Rating Scale. We investigated the correlation between the PROMIS Mobility and other tools to assess use in this population and any clustering of outcome scores. Results: There was a strong correlation between the PROMIS Mobility and other established PROMs; NAHS ( rs = 0.79; p < 0.001). There was notable clustering in PROMIS at the upper end of the distribution score (42.5%), with less seen in the NAHS (20.3%). However, the clustering was broadly similar between PROMIS Mobility and the comparable domains of the NAHS; function (53.6%), and activity (35.0%). Conclusion: PROMIS Mobility strongly correlated with other tools demonstrating convergent construct validity. There was clustering of physical function scores at the upper end of the distributions, which may reflect truncation of the data caused by participants having excellent outcomes. There were elements of disease not captured within PROMIS Mobility alone, and difficulties in differentiating those with the highest levels of function. Cite this article: Bone Jt Open 2021;2(12):1089–1095.